Preparation and Study of Multi-Heteroatom Carbon Nanotube as Excellent Electrocatalyst for Oxygen Reduction Reaction Using Polydopamine Derivative - Jian Yang; Lihong Niu; Zhijun Zhang; Liang Yan; Lingjun Chou (Advances in Materials Science and Engineering)
F and other heteroatom codoped multiwalled carbon nanotubes as nonmetal electrocatalyst were developed through pyrolysis of polydopamine derivative under high temperature. The influence of the amount and type of heteroatom on the catalytic activity was investigated. Especially, N/S/F-codoped carbon nanotubes exhibit the most excellent electrocatalytic activity for oxygen reduction reaction and stability. The method afforded an excellent building block to universally design multi-heteroatom-doped or F-doped carbon materials for ORR or other energy-relevant applications.